Perceived causes of adverse pregnancy outcomes and remedies adopted by Kalenjin women in rural Kenya - Roselyter Monchari Riang'a; Anne Kisaka Nangulu; Jacqueline E. W. Broerse (BMC, 2018)
Abstract Background There have been few studies about the basis on which women in developing regions evaluate and choose traditional rather than western maternal care. This qualitative study explores the socio-cultural perceptions of complications associated with pregnancy and childbirth and how these perceptions influence maternal health and care-seeking behaviours in Kenya. Methods Kalenjin women (n = 42) aged 18-45 years, who were pregnant or had given birth within the last 12 months, were interviewed. A semi-structured interview guide was used for data collection. A further nine key informant interviews with Traditional Birth Attendants (TBAs) who were also herbalists (n = 6), community health workers (CHWs) (n = 3) and a Maternal and Child Health (MCH) nursing officer (n = 1) were conducted. The data were analysed using MAXQDA12 software and categorised, thematised and analysed based on the symbolic dimensions of Helman's (2000) ill-health causation aetiologies model. Results Pregnancy complications are perceived as the consequence of pregnant women not observing culturally restricted and recommended behaviour during pregnancy, including diet; physical activities; evil social relations and spirits of the dead. These complications are considered to be preventable by following a restricted and recommended diet, and avoiding heavy duties, funerals, killing of animals and eating meat of animal carcasses, as well as restricting geographical mobility, and use of herbal remedies to counter evil and prevent complications. Conclusion Delay in deciding to seek maternal care is a result of women's failure to recognise symptoms and maternal health problems as potential hospital cases, and this failure stems from culturally informed perceptions of symptoms of maternal morbidity and pregnancy complications that differ significantly from biomedical interpretations. Some of the cultural maternal care and remedies adopted to prevent pregnancy complications, such as restriction of diet and social mobility, may pose risks to the pregnant woman's health and access to health facilities whereas other remedies such as restricting consumption of meat from animal carcasses and heavy duties, as well as maintaining good social relations, are cultural adaptive mechanisms that indirectly control the transmission of disease and improve maternal health, and thus should not be considered to be exclusively folk or primitive.